Evaluation of the Implementation of Electronic Procurement of Goods and Services (E-Procurement) - Komang Elistrisia Milandari; I Gusti Agung Adnyana Putera; Dewa Ketut Sudarsana (International Journal Labs, 2026)
Electronic procurement (e-procurement) is widely implemented to improve transparency, efficiency, and accountability in public procurement. However, its implementation still faces various technical and administrative constraints that affect procurement performance in local governments. This study evaluates the implementation of e-procurement in the Procurement of Goods and Services (PUPRPKP) Office of Tabanan Regency for the 2022–2024 period, identifies implementation barriers, and formulates alternative improvement strategies. A qualitative descriptive approach was employed. Data were collected through structured interviews with procurement working groups, Commitment Making Officials, and service providers, supported by SPSE system observations and document analysis. Data were analyzed using an interactive model with purposive sampling. Findings show implementation is adequate but not yet optimal in meeting procurement principles. Efficiency shows time and cost savings, constrained by system instability and administrative duplication. Effectiveness is limited by SiRUP delays and price-based evaluation dominance. Transparency and accountability are generally applied, but monitoring and data consistency are weak. Competition is hindered by specification bias and low participation. Study concludes e-procurement in Tabanan is not yet optimal and requires strengthening infrastructure, system integration, regulation, and oversight to ensure compliance.